The advanced ply placement process – an innovative direct 3D placement technology for plies and tapes. (2nd January 2017) - Szcesny, Marko; Heieck, Frieder; Carosella, Stefan; Middendorf, Peter; Sehrschön, Harald; Schneiderbauer, Michael
Abstract: Breaking down the cost structure of state-of-the-art CFRP part shows that a major share of the costs is caused by labor and equipment as well as process energy consumption. Therefore, the main goal of the EU funded FP7 project LOWFLIP (Low CostFl exibleI ntegrated CompositeP rocess) has been the reduction of these costs by introducing new technologies into CFRP production processes. The LOWFLIP concept focuses on three main aspects: Development of a new out-of-autoclave (OOA) prepreg system with snap cure capabilities. Development of a direct 3D placement technology for plies and tapes. Development of energy efficient and fast heating toolings. The main content of this paper is detailed information on a novel direct 3D prepreg layup process for automated production of large-scale fiber reinforced parts of small and medium lot sizes. The advanced ply placement process, which is able to drape and compact unidirectional prepreg tapes with currently up to 300 mm ply width directly into a double curved tooling, is being introduced. Two large-scale demonstrator parts from the transport and aerospace sector will be presented. Experiences gained during prototype manufacturing will be reflected and benchmarks of the equipment are presented. Abstract :